To determine which equation can be solved by first adding six and then dividing by negative three, we will analyze each option.
-
-3x - 6 = -9:
- If we add 6 to both sides, we get -3x = -3.
- Then dividing by -3 gives x = 1.
-
x / -3 + 6 = -9:
- If we subtract 6 from both sides, we get x / -3 = -15.
- Dividing by -3 at this stage does not hold.
-
6 - 3x = -9:
- If we add 6 to both sides, we get 6 - 3x + 6 = -3. This changes the situation considerably and does not lead us to a clearer division by -3.
-
3x - 6 = -9:
- If we add 6 to both sides, we get 3x = -3.
- Dividing by 3 will yield x = -1.
Since the task specifies adding six and then dividing by negative three, the best-fit option we can solve straightforwardly is:
- -3x - 6 = -9
Thus, the equation you could solve by first adding six and then dividing by negative three is: -3x - 6 = -9.